MODELING OF INTELLIGENT SORTING MANIPULATORS FOR MULTI-PRODUCT PRODUCTION LINES - A. O. Yoqubjonov (Journals Park Publishing, 2025)
This article presents the modeling and prototyping stages of an intelligent sorting manipulator system designed for multi-product production lines. During the sorting process, the manipulator performs tasks such as detecting, classifying, and directing objects of various sizes and weights to the appropriate paths. Mechanical and kinematic models of the system were developed using SolidWorks and MATLAB software, while a physical prototype was assembled using Arduino UNO and sensor modules. The sorting accuracy and time were analyzed by comparing simulation and practical experiment results. The outcomes demonstrate that this technology can operate efficiently in multi-product manufacturing and contribute to increasing the level of automation.
Keywords: Intelligent manipulator, Sorting system, Simulation, Arduino, Sensor integration, Robotics.